SIRT6 promotes mitochondrial fission and subsequent cellular invasion in ovarian cancer. Issue 9 (24th June 2022) - Bandopadhyay, Shreya; Prasad, Parash; Ray, Upasana; Das Ghosh, Damayanti; Roy, Sib Sankar
Abstract : Ovarian cancer ranks fifth in terms of cancer mortality in women due to lack of early diagnosis and poor clinical management. Characteristics like high cellular proliferation, EMT and metabolic alterations contribute to oncogenicity. Cancer, being a "metabolic disorder, " is governed by various key regulatory factors like metabolic enzymes, oncogenes, and tumor suppressors. Sirtuins (SIRT1‐SIRT7) belong to the group of NAD + deacetylase and ADP‐ribosylation enzymes that function as NAD + sensors and metabolic regulators. Among sirtuin orthologs, SIRT6 emerges as an important oncogenic player, although its possible mechanistic involvement in ovarian cancer advancement is still elusive. Our data indicated a higher expression of SIRT6 in ovarian cancer tissues compared with the non‐malignant ovarian tissue. Further, we observed that overexpression of SIRT6 enhances glycolysis and oxidative phosphorylation in ovarian cancer cells. The energy derived from these processes facilitates migration and invasion through invadopodia formation by reorganization of actin fibers. Mechanistically, SIRT6 has been shown to promote ERK1/2‐driven activatory phosphorylation of DRP1 at serine‐616, which has an obligatory role in inducing mitochondrial fission. These fragmented mitochondria facilitate cell movement important for metastases. siRNA‐mediated downregulation of SIRT6 was found to decrease cellular invasion through compromised mitochondrial fragmentation and subsequent reduction in stress fiber formation in ovarian cancer cells. Thus, the present report establishes the impact of SIRT6 in the regulation of morphological and functional aspects of mitochondria that modulates invasion in ovarian cancer cells. Abstract : SIRT6 is highly expressed in ovarian cancer cells and regulates tumor cell invasion. SIRT6 enhances the glycolytic rate and oxidative phosphorylation in ovarian cancer cells. SIRT6 induces phospho‐ERK1/2 mediated DRP1 phosphorylation at serine‐616 to facilitate mitochondrial fission. Fragmented mitochondria translocate in an anterograde manner along with actin fibers to facilitate invadopodia formation and associated cancer cell movement.